M-estimate like correlation based algorithm for direction of arrival estimation under alpha-stable environments - Jin-feng ZHANG; Tian-shuang QIU; Ai-min SONG; Hong TANG; Na WANG (Tongxin xuebao)
A novel class of bounded statistics,namely,the M-estimate like correlation (MELC) for independently identi-cal distributed symmetric alpha-stable (SαS) random variables was defined.Based on the MELC matrix for the array sensor outputs,a new algorithm for direction of arrival (DOA) estimation in the presence of complex SαS noise was proposed.The comprehensive Monte-Carlo simulation results show that the MELC-MUSIC algorithm not only outper-forms the fractional lower order statistics (FLOS) based MUSIC algorithms under low SNR conditions and multi-source signals environment,but also is robust with circular and noncircular signals.